(The Influence of Preparation Time of Enzymes Fermentation for the Quality of Modified Cassava Flour (MOCAF) - Tita Aviana; H G Pohan; Reno Fitri Hasrini (Balai Besar Industri Agro, 2011)
Cassava (Manihot esculenta) also called yuca or cassava, is a native plant of south America. cassava is used as an alternative staple food source of carbohydrate .in indonesia one cassava intermediate products is mokaf (modified cassava flour ) whivh is made through fermentation time which are 2 hours (S2)and 24 hours (S24 and P24) and studied their characteristics (moisture ,fibre, ash and flour characteristics including gelatinization characteristic and gel strength) according to analysis including gelatinization characteristics mokaf with 2 hours enzyme preparation time has lower viscosity and gel strength in proximate analysis results ,mokaf with 2 hours enzyme preparation time have a tendency of smaller levels of ash and crude fiber ,buthigher protein. the best treatment for mocaf preparation is 24 hours pra-fermentation followed with fermentation and spinning process before drying ,which produce mokaf with 0,51% ash, 1,88% crude fiber ,0,86% protein and 0,66% fat.